Perbandingan Perolehan Daya Solar Panel Monocrystalline Terhadap Solar Panel Polycrystalline - Pratama, Ervan; Watiasih, Richa (ELKHA : Jurnal Teknik Elektro, 2020)
The availability of two types of solar panels that are common in the market namely monocrystalline and polycrystalline types cause confusion in the selection so that many solar panel users are questioning the differences of these two types of solar panel. This study produced a data logger system using Arduino Uno R3 to control voltage, current and temperature sensors for logging data that stores power measurement data from monocrystalline and polycrystalline solar panel in a micro SD. After it we can manage data to compare power produced between two types the solar panel. From the results of testing this data logger system it can be seen that monocrystalline solar panel are 9.18% better on power produced than polycrystalline when the maximum power conversion is generated.